2006
DOI: 10.1103/physrevd.73.063508
|View full text |Cite
|
Sign up to set email alerts
|

Loop cosmological dynamics and dualities with Randall-Sundrum braneworlds

Abstract: The discrete quantum geometric effects play an important role in dynamical evolution in the loop quantum cosmology. These effects which are significant at the high energies lead to the quadratic energy density modifications to the Friedmann equation, as in the Randall-Sundrum braneworld scenarios but with a negative sign. We investigate the scalar field dynamics in this scenario and show the existence of a phase of super-inflation independent of the inverse scale factor modifications as found earlier. In this … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
140
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 133 publications
(141 citation statements)
references
References 71 publications
(92 reference statements)
1
140
0
Order By: Relevance
“…It is remarkable that the origin of ρ crit is purely quantum, since in the classical limit → 0 one has ρ crit → ∞. In addition, it should be noted that, interestingly, ρ 2 modifications also appear in string inspired braneworld scenarios and it has been shown that there exist interesting dualities between the two frameworks [16]. Such modifications in braneworlds, however, are usually positive definite so that a bounce is absent, unless the existence of two timelike extra dimensions is assumed [20,21].…”
Section: Effective Dynamics In Loop Quantum Cosmology and Big Bounce mentioning
confidence: 99%
See 3 more Smart Citations
“…It is remarkable that the origin of ρ crit is purely quantum, since in the classical limit → 0 one has ρ crit → ∞. In addition, it should be noted that, interestingly, ρ 2 modifications also appear in string inspired braneworld scenarios and it has been shown that there exist interesting dualities between the two frameworks [16]. Such modifications in braneworlds, however, are usually positive definite so that a bounce is absent, unless the existence of two timelike extra dimensions is assumed [20,21].…”
Section: Effective Dynamics In Loop Quantum Cosmology and Big Bounce mentioning
confidence: 99%
“…Though the issue of super-inflation in LQC has been discussed widely in the literature (see, e.g., [16,18,23,24]), we still make some analyses here for maintaining this paper selfcontained. Besides, we discuss the effective behavior of a quintom matter in the inflation process in this subsection.…”
Section: Super-inflation and Effective Quintommentioning
confidence: 99%
See 2 more Smart Citations
“…The general formula of loop quantum gravity, which takes into account the discrete nature of space-time, expresses the Hamiltonian in terms of the holonomies h j (λ) ≡ e −i λβ 2 σj , where σ j are the Pauli matrices [45,50] …”
Section: Modified Friedmann Equationsmentioning
confidence: 99%